2018
DOI: 10.1002/mpr.1740
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Prodromal Questionnaire–Brief in a representative sample of adolescents: Internal structure, norms, reliability, and links with psychopathology

Abstract: The PQ-B is a brief, easy, and reliable tool for screening psychotic-like experiences in adolescents from the general population. The assessment of risk for psychosis and its relationship with other psychopathological risk factors in a close-in strategy or two-stage process model may help us to enhance the early identification for youths at heightened risk for serious mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 63 publications
9
13
1
Order By: Relevance
“…These results differed from a previous study by Fonseca-Pedrero et al ( 28 ), where PQ-B item endorsement showed strong measurement invariance across gender among community adolescents. Nevertheless, they simultaneously report large gender effects for items 7 and 20 in a separate differential item functioning (DIF) analysis, and we thus replicated their results for item 7, despite a different age group and language version.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results differed from a previous study by Fonseca-Pedrero et al ( 28 ), where PQ-B item endorsement showed strong measurement invariance across gender among community adolescents. Nevertheless, they simultaneously report large gender effects for items 7 and 20 in a separate differential item functioning (DIF) analysis, and we thus replicated their results for item 7, despite a different age group and language version.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the assessment of measurement invariance is especially critical across groups that have been found to differ in the trait of interest. Among studies addressing PLEs questionnaires, measurement invariance has been demonstrated across gender ( 27 , 28 ), an encouraging result which warrants replication. When extending the concept of PLEs to include schizotypy, results have been mixed with regards to ethnicity ( 29 32 ), and the non-invariance between ethnic groups may wholly or in part be explained by language version differences ( 31 ).…”
Section: Introductionmentioning
confidence: 83%
“…As the participants recruited in this study were college students with an age range of 14 to 31 years, while NAPLS recruited clinician-referred subjects aged 12 to 35 years, SHARP included helpseeking subjects aged 15 to 45 years, and RAP included help-seeking subjects aged 12 to 22 years. Similar to previous studies using PQ-B to screen CHR in Chinese population [16,22,[45][46][47], our research proved that PQ-B could be a feasible rst-step instrument for screening suspected CHR subjects in college students. Both the sensitivity and speci city of PQ-B were excellent in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to previous studies using PQ-B to screen CHR in Chinese population [16,22,[45][46][47], our research proved that PQ-B could be a feasible rst-step tool to detect suspected CHR subjects in college students.…”
Section: Discussionsupporting
confidence: 85%